Ancient Egyptian furniture : Volume II: Boxes, chests and footstools - Killen, Geoffrey (Oxbow Books, 2017)
Title; Copyright; Contents; List of Figures; List of Plates; Acknowledgements; Abbreviations and Sigla; Chapter 1. The Earliest Examples; Chapter 2. Remains of Old Kingdom Boxes; Chapter 3. Middle Kingdom Boxes; Chapter 4. Boxes of the New Kingdom; Chapter 5. Perpaut and Kha Collections; Chapter 6. The Yuia and Thuiu Collection; Chapter 7. The Tutankhamun Collection; Chapter 8. Ramesside and Late Period Boxes; Chapter 9. Footstools; Catalogue of Museum Collections; Bibliography; Plate section.